Association of miR-149 gene rs2292832 polymorphism with necrotizing enterocolitis in preterm infants - Hong Qiu; Xiaojun Wang; Yanhong Li; Renping Mao; Qin Lv (The Turkish Journal of Pediatrics)
Background. Necrotizing enterocolitis (NEC) is a prevalent and challenging intestinal disease in premature infants, lacking a specific pathogen consistently associated with its occurrence. Effectively preventing and treating NEC to reduce mortality rates remains a significant contemporary challenge. The present study aimed to explore the correlation between microRNA-149 gene polymorphism and NEC in premature infants in a Chinese Han population.